Habersham family papers
Correspondence, chiefly of the sons of Richard Wylly Habersham (1786-1842). Chiefly letters between Rev. Barnard Elliott Habersham, his wife Emma Matthews Habersham, and their son, Richard Wylly Habersham, who served in the Hampton Legion of the Confederate Army and settled in Brazil after the Civil War. Includes letters from Alexander Wylly Habersham, who resigned from the U.S. Navy in 1857 to pursue mercantile interests in Japan and was imprisoned at Fort McHenry, Baltimore, Md., as a Southern sympathizer after his return in 1861; and some letters from the related Barker family of New York and the Pacific Northwest.
Georgia family headed by Richard Wylly Habersham (1786-1842), lawyer and U.S. representative from Georgia, and including his four sons: Richard Wylly Habersham (b.1812), artist; the Rev. Barnard Elliott Habersham; Alexander Wylly Habersham, U.S. naval officer and merchant in Japan; and Stephen Elliott Habersham, physician.
Collection material in English.
Keywords: Habersham, Alexander Wylly, -- 1826-1883 -- Correspondence; Habersham, Barnard Elliott, -- 1814- -- Correspondence; Habersham, Emma Matthews -- Correspondence; Habersham, Richard Wylly -- Correspondence; Habersham, Richard Wylly, -- 1786-1842 -- Correspondence; Habersham, Richard Wylly, -- 1812- -- Correspondence; Habersham, Stephen Elliott, -- 1821- -- Correspondence; Barker family -- Correspondence; Habersham family; Confederate States of America. -- Army. -- Hampton Legion; United States. -- Navy -- Officers; Allegiance -- United States; American Confederate voluntary exiles -- Brazil; Artists -- Georgia; Clergy -- Georgia; Merchants -- Japan; Physicians -- Georgia; Prisoners -- Maryland -- Baltimore; Prisons -- Maryland -- Baltimore; Fort McHenry (Baltimore, Md.); Georgia -- History -- Civil War, 1861-1865.; Georgia -- Politics and government -- 1775-1865.; Georgia -- Social life and customs; Japan -- Commerce -- United States; Maryland -- History -- Civil War, 1861-1865.; New York (State) -- Social life and customs; Northwest, Pacific -- Social life and customs; United States -- Commerce -- Japan; United States -- History -- Civil War, 1861-1865 -- Prisoners and prisons